EVALUATION OF CLOUD TO GROUND FLASH DENSITY OF 150 KV TRANSMISSION LINE BETWEEN PARIT BARU SUBSTATION AND SENGGIRING SUBSTATIO - Manalu, Ayub Rainaldo; Danial, Danial; Rajagukguk, Managam (Telecommunications, Computers, and Electricals Engineering Journal (TELECTRICAL), 2024)
SUTT is a high voltage overhead line with a power of 70 kV - 150 kV to distribute electric power from the generating center to the substation or from substation to substation. The purpose of this study was to obtain modeling of lightning strike density on the 150 kV transmission line between Parit Baru substation and Senggiring substation using geostatistical approaches, namely IDW methods (Inverse Distance Weighted). In identifying the level of vulnerability to lightning strikes, Cloud to Ground lightning event data (2018"“2020) is used. The aim of this research is to obtain the density pattern of lightning strikes on the 150 kV transmission line between the Parit Baru substation and the Senggiring substation. The process in ArcGIS 10.8 software aims to obtain lightning strike density and display the results of the lightning strike density map. Based on the results of data processing for 3 years, the highest density of lightning strikes occurred in 2019 in Segedong District at 54.52 strikes/km ². Meanwhile, the lowest density of lightning strikes occurred in 2018 in East Mempawah District, amounting to 2.86 strikes/km ². Based on the lightning strike density map per grid on the 150 kV transmission line between Parit Baru substation and Senggiring substation for 3 years, the results obtained for the highest lightning strike were 36 strikes/km ² while for the lowest strike it was 1 strike/km ². From this research, it was found that there were 15 transmission towers that passed a high density of lightning strikes with a strike range of 25"“36 strikes/km ² and the highest lightning strike occurred at tower number 31, number 30, and number 29, amounted to 36 strikes/km ².